RP-HPLC Method Development and Validation for Estimation of Nivolumab in Marketed Formulations - Maithani, M.; Dwivedi, D.; Rawat, V. (Journal of Biomedical and Pharmaceutical Research, 2022)
A simple and precise RP-HPLC method for the estimation of Nivolumab in marketed dosage forms was developed and validated. The chromatographic separation of the drug was done with a Waters Sun Fire C8 Column (250 mm × 4.6 mm i.d., particle size 5 μ) using 0.3% TFA, acetonitrile and methanol (45:35:20 v/v/v) as a mobile phase. The instrument was set at flow rate of 1.2 mLmin-1 at ambient temperature and the wavelength of UV-visible detector was 230nm. The method showed excellent linearity over a range of 10-250 μgmL-1 for the drug. The correlation coefficient for Nivolumab was noted to be 0.9998. The mean recovery values were found to be 99.38% and 99.90%. The results suggest that the proposed method could be suitable for quantitative determination of Nivolumab in pharmaceutical preparations and also for quality control in bulk manufacturing. The f-test and t-test at 95% confidence level were applied on data for statistical analysis.